Efficacy of Habb-e-Sandroos in Internal Hemorrhoids: An openlabelled single-arm clinical study - Fatimah , Mehjabeen; Alam , Mahfooz; Malik, Rabia; Shah Alam , S; Lone, Showkat Bashir; Ahmad Bhat, Muzafar Din (Bangladesh Journal of Medical Science, 2025)
Aim Hemorrhoids are one of the most common anorectal complaints reported in anorectal clinics with an estimated prevalence of 4.4% in the United States and 13-36% in the United Kingdom. It is one of the oldest diseases known to mankind with history seen in the ancient medical writings of every culture, including Babylonian, Hindu, Greek, Egyptian, and Hebrew. According to the Unani system of medicine, the cause of hemorrhoids is morbid Khilt-e- Sauda (black bile). Habb-e-Sandroos has hemostatic, astringent, desiccant, laxative, and anti-inflammatory activity and since ages used by Unani physicians to treat hemorrhoids, hence present study aimed to evaluate its effect in Internal hemorrhoids. Methods This single-arm open-labelled clinical trial was conducted among 30 male and female patients, aged 20 to 65years, with 1st and 2nd degree hemorrhoids confirmed by proctoscopy. Habb-e- Sandroos, 2 tablets each weighing 0.5g was given thrice a day for 45 days. The efficacy outcome was assessed by an arbitrary grading scale. Results: Significant changes were observed in efficacy outcomes. Follow up assessments were done on every fortnightly for the first forty-five days and monthly follow-up for two months without treatment. Study showed that Habbe- Sandroos produced significant improvement in subjective parameters; bleeding per rectum (p <0.001), prolapse of pile mass (p <0.001), mucus discharge per-rectum (p=0.026), and itching per rectum (p =0.003) at 2 months from the baseline scores. Drug has promising results in Internal hemorrhoids and warrants further studies. Conclusion The result inferred that the test drug is safe and effective in improving the severity of symptoms of Internal hemorrhoids of 1st and 2nd Grade. It can be used as an alternate to conventional treatment. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 222-229